Technology of Gallium Nitride Crystal Growth - Ehrentraut, Dirk.; Meissner, Elke.; Bockowski, Michal; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book deals with the important technological aspects of the growth of GaN single crystals by HVPE, MOCVD, ammonothermal and flux methods for the purpose of free-standing GaN wafer production. Leading experts from industry and academia report in a very comprehensive way on the current state-of-the-art of the growth technologies and optical and structural properties of the GaN crystals are compared.
Market for Bulk GaN Crystals -- Development of the Bulk GaN Substrate Market -- Vapor Phase Growth Technology -- Hydride Vapor Phase Epitaxy of GaN -- Growth of Bulk GaN Crystals by HVPE on Single Crystalline GaN Seeds -- Freestanding GaN Wafers by Hydride Vapor Phase Epitaxy Using Void-Assisted Separation Technology -- Nonpolar and Semipolar GaN Growth by HVPE -- High Growth Rate MOVPE -- Solution Growth Technology -- Ammonothermal Growth of GaN Under Ammono-Basic Conditions -- A Pathway Toward Bulk Growth of GaN by the Ammonothermal Method -- Acidic Ammonothermal Growth Technology for GaN -- Flux Growth Technology -- High Pressure Solution Growth of Gallium Nitride -- A Brief Review on the Na-Flux Method Toward Growth of Large-Size GaN Crystal -- Low Pressure Solution Growth of Gallium Nitride -- Characterization of GaN Crystals -- Optical Properties of GaN Substrates -- Point Defects and Impurities in Bulk GaN Studied by Positron Annihilation Spectroscopy.
Keywords: Physics; Crystallography; Optical materials; Physics; Crystallography; Optical and Electronic Materials